Strategic recovery and enhancement of natural resources and environment post-Mount Semeru eruption in Lumajang Regency - Hargono, Arief; Prihatiningtyas, Wilda; Prasasti, Corie Indria; Kuncoro, Eko Prasetya; Adriyani, Retno; Hartono, Rudy; Kurnia, Galuh Mega (Journal of Community Empowerment for Health, 2025)
Introduction: Mount Semeru experienced a pyroclastic flow in 2021. Volcanic material was observed heading towards Lumajang Regency. Natural resources and the environment were significantly affected by the eruption of Mount Semeru. The eruption can have both short-term and long-term impacts on the surrounding natural resources and environment. In 2023, the National Disaster Management Authority (NDMA) in collaboration with Master of Disaster Management, Postgraduate School of Universitas Airlangga (MDM PGS UNAIR) implemented the Assistance for Recovery and Productivity Improvement of Natural Resources and Environment (ARPINRE) program in the areas affected by the Mount Semeru eruption, namely Lumajang Regency, East Java Province. This article aims to report the results of the ARPINRE program in Lumajang Regency.Methods: The disaster-prone area assistance was carried out based on various theories and approaches related to disaster management. These include Disaster Management, Water, Air, Sanitation, and Health (WASH) along with indicators from SPHERE.Results: Before conducting the assistance, the team conducted a study of inventory and prioritization of issues. Technical guidance activities were conducted as a follow-up to the established interventions. There were three technical guidance (I, II, III). Based on the results of pre-tests and post-tests distributed to technical guidance participants, as well as interviews with the self-sustaining community (SSC), it was concluded that there was an increase in public understanding of the importance of waste sorting and management through Integrated Waste Management Sites (IWMS) and the importance of biopores as a means of water conservation and composting. Stimulus provision, an integral part of this activity, was also carried out alongside technical guidance III. Evaluation results showed an increase in the average pre-test score from 52.67 to 65.33 in the post-test.Conclusions: Despite this increase, the average score remained low. Continued socialization about solid waste management is necessary.